Transformasi Partisipasi Politik Masyarakat Desa melalui E-Voting dalam Pemilihan Kepala Desa di Desa Sibolangit, Kecamatan Merek - Hera Septiana Siahaan; Julia Ivanna (Journal on Education, 2024)
This study aims to examine the transformation of political participation in the village community through e-voting in the election of village heads in Sibolangit Village, Merek Subdistrict. The research method used is qualitative, employing data collection techniques such as interviews, observations, and document analysis. The research participants include village residents, election organizers, and local authorities. The findings reveal that the implementation of e-voting has significantly transformed political participation among the village community. E-voting has increased voter turnout, streamlined the voting process, and enhanced transparency and accountability in the election process. Additionally, it has empowered marginalized groups, such as women and youth, by providing them with easier access to participate in the electoral process. However, challenges such as digital literacy gaps and concerns over cybersecurity need to be addressed to ensure the effectiveness and inclusivity of e-voting. Overall, e-voting has the potential to democratize the electoral process and strengthen grassroots democracy in Sibolangit Village.